A 'turn-on' fluorescent probe for lysosomal phosphatase: a comparative study for labeling of cancer cells. Issue 27 (29th June 2018) - Podder, Arup; Senapati, Sudipta; Maiti, Pralay; Kamalraj, Devaraj; Jaffer, Syed S; Khatun, Sabina; Bhuniya, Sankarprasad
Abstract : A turn-on fluorescent probe (LP1 ) discriminates cancer cells from normal cells based on expression of phosphatase in lysosomes. Abstract : We have described the ability of a newly synthesized fluorescent probe (LP1 ) to detect phosphatase activity in lysosomes in cancer cells. ProbeLP1 displayed a 33-fold fluorescence intensity enhancement at λ em 532 nm in the presence of phosphatase in HEPES buffer (pH 4.5). The quantum yield of probeLP1 was increased by ∼21-fold upon exposure to phosphatase at acidic pH. The probeLP1 is highly chemoselective toward phosphatase (ALP/ACP) and is insensitive to interference by ubiquitous biological analytes. The high cell adhesion property and cell viability ofLP1 indicate thatLP1 is biocompatible and nontoxic; these two characteristic features make it a suitable candidate for phosphatase tracking in living cells.LP1 dose-dependent fluorescence images in living cells suggested that the expression of phosphatase in cancer cells (HeLa) is 2-fold higher as compared to the normal NIH-3T3 cells. The colocalization images confirmed thatLP1 was exclusively localized in lysosomes. We envision thatLP1 could be a potential tool in clinical diagnosis for discriminating cancer cells from normal cells depending on the expression of phosphatase in lysosomes.